Hasan Al-Turabi's Expansive Logic: A New Approach to the Development of Indonesian Ushul Fiqh - Khoiri, M. Alim; Maknun, Moch Lukluil; Muntakhib, Ahmad; Munjiyat, Munjiyat (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The interdisciplinary field of uṣūl al-fiqh has to come to terms with the difficulties that arise from the consequences of dynamic socio-technology and political changes. While most classical methodologies (especially qiyās and istishāb) tend to become overly focused on cause and text, with little to no attention to the context. There have been a number of studies on Hasan Al-Turabi's legal and political thought, while attention has been scarce for the integration of his reconstruction of qiyās and istishāb, particularly with regard to the development of uṣūl al-fiqh in Indonesia. This study aims to analyze Al-Turabi's concept of expansive logic, particularly in relation to al-qiyās al-wāsiʿ and al-istishāb al-wāsiʿ, and its methodological implications for Islamic legal reasoning in Indonesia. Based on qualitative library research and thematic content analysis of Al-Turabi's main works, the study aims to recover the epistemological and operational foundations of his legal reasoning. The study implied that Al-Turabi's expansive logic constitutes a methodological reconstruction of maqāṣid in such a way that it is not limited to an ‘illah’ based restrictive analogy or an unchanging legal continuity but incorporates justice, public welfare, and social context. Local Indonesian thought reflects sophisticated engagement with the legal nationalism of Hasbi ash-Shiddieqy and Hazairin in respect to contemporary legal issues and ijtihād. This scholarship locates expansive logic and interdisciplinary engagement as a plausible methodological pivot, situating Islamic legal thought in the Middle East alongside innovations in uṣūl al-fiqh in Indonesia.